Amphidiploids Derived from Thinopyrum bessarabicum (Savul. & Rayss) Á. Löve (Poaceae) to Enhance Grain Yield Under Drought and Heat-Drought Stress - Antim; Tyagi, Bhudeva Singh; Ojha, Ashish; Nain, Ashish; Sheoran, Sonia; Singh, Vikram; Singh, Gyanendra; Kamboj, Mehar Chand (Journal of Cereal Research, 2024)
In the present study, Thinopyrum bessarabicum [(Savul. & Rayss) Á. Löve (Poaceae)], known for its rust resistance and heat tolerance traits, was incorporated into a breeding program. Seven different durum (AABB) and two bread (AABBDD) wheat cultivars were carefully chosen as recipient parents for improvement in abiotic stress tolerance traits. The resultant fixed lines were rigorously examined for a range of agronomic and physiological traits during the rabi seasons of 2019 and 2020 in four environments for two consecutive years across two locations, Hisar and Karnal, Haryana. Analysis using AMMI and GGE methods, focusing on grain yield per plot (kg/plot) across multiple environments, revealed that these amphidiploids exhibited superior performance in E4>E3>E2>E1, signifying that their average performance excelled under heat and drought stress conditions. All nine amphidiploids demonstrated their best performance in Hisar under drought and temperature stress. Among these, EC787014 (T. aestivum L. cv. Chinese Spring X Th. bessarabicum) emerged as the top-performing genotype in both years for the heat and drought stress environment (E4), with an average yield of 0.506 kg/plot in 2019 and 0.494 kg/plot in 2020.